TECHNOLOGICAL INNOVATION IN THE MANAGEMENT OF HAJJ AND UMRAH: TOWARDS SERVICE EXCELLENCE IN THE DIGITAL ERA - Ratu Amalia Hayani; Mujahidin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The digital era has brought significant changes in various aspects of life, including in the management of Hajj and Umrah. The research method in this study is literature. The results show that technological innovations have contributed to increased efficiency, safety, and comfort for pilgrims, as well as enabling more structured management for the organising authority. These technologies facilitate easier access to information, real-time guidance, eflective crowd management, and resource optimisation. Thus, technological innovations have great potential to improve Hajj and Umrah services, but their implementation must be done carefully to ensure they enrich, rather than disrupt, the pilgrims' spiritual experience.